PELATIHAN PENGENALAN PERANGKAT KERAS DAN PERANGKAT LUNAK KOMPUTER UNTUK SISWA-SISWI SDN 1 DESA BATU TEGI KECAMATAN AIR NANINGAN - Zainal Ansori; Yulmaini Yulmaini (Institut Informatika dan Bisnis Darmajaya, 2019)
Today, technology is growing and the use of technology should be introduced to learners as early as possible such as introducing the basics of hardware and computer software. The introduction of more detailed computer from an early age needs to be done to the schools. SDN 1 Pekon Batu Tegi is one of the primary schools located in the district of Air Naningan Tanggamus Regency. The introduction of computers given to students is the foundation for hard work and computer software. The purpose of this activity is so that the students of SDN 1 Pekon Batu Tegi know and know more about hardware computer and its function. Introduction of hardware and software is expected to help elementary school students know more details about the names of computer components and software used therein.Keywords : Training, Introduction of Computer